(untitled) (Balneo and PRM Research Journal, 2021)
Introduction. The study aims to assess the antinociceptive and anti-inflammatory activity of extracts obtained from indigenous species of wormwood: Artemisia absinthium, A. annua, A. vulgaris and A. pontica. Materials and methods. For these experiments, we employed nociception models using thermal stimulus (hot plate and tail immersion tests, t = 52.5 0C; 30, 60 and 90 minutes testing), chemical stimulus (Zymosan-induced abdominal constriction response test, using distinct lots and testing at 60, 90 and 120 minutes after administration of samples) and pressure stimulus (Randall Selitto test) and an inflammation model for the evaluation of inflammatory edema by Plethysmometer test. Groups of 6 Swiss mice / lot were used, receiving by oral administration the plant extracts suspended in 0.1% CMC-Na. The doses were administered in geometric progression. Chemical analyses were performed by HPLC-MS in order to identify bioactive substances present in extracts: methoxylated flavonoids, sesquiterpene lactones, phytosterols and hydroxycinnamic acids. Results and discussion. All plant extracts showed antinociceptive action on the models with thermal stimulus, as demonstrated by the ED50 values obtained at different test times. In the models of nociception with chemical and mechanical stimulus, models based on inflammatory mediation, the studied fractions have partially proved their antinociceptive action. Regarding the degree of inhibition of inflammatory edema, the highest potency was exhibited by Artemisia pontica extract (86.5% inhibition for the dose of 100 mg/kg). Hispidulin and eupatorin, known anti-inflammatory compounds, were identified in all extracts, along with caffeic and chlorogenic acids, stigmasterol, campesterol and β-sitosterol.